RESEARCH OF RATIONAL CHARACTERISTICS OF THE DATE COMMUNICATION LINKS OF THE INFORMATION AND MEASURING SYSTEM - Kliushnyk, I. A. (Science and Transport Progress, 2018)
Purpose. The article focuses on determining the rational parameters of data transmission interfaces for information and measuring system for testing the hydraulic transmissions, as well as determining the degree of fault to-lerance in various operating modes of the system. Methodology. In the study the researcher has determined and theoretically calculated the main characteristics of the data transmission channels from the hardware converters of the data signals of analog sensors of technological parameters to the computer. For a more complete assessment, an imitation model was created in the MATLAB environment to study the assigned task. Analysis of the results obtained from the theoretical calculations and using the simulation data model to determine the rational settings of interfaces (rational transmission speed, rational element base, rational system structure, etc.) of data transmission makes it possible to determine the rational characteristics of the system. Findings. For the existing information-measuring system for testing hydraulic locomotive transmission of diesel locomotives, studies were carried out to determine and theoretically calculate the main characteristics of the data transmission channels from the hardware converters of data signals from analog sensors of technological parameters to the computer. To study the tachometric subsystem, an imitation model was created that allowed to investigate the main characteristics of the data transmission channels from the hardware converters of data signals of analog sensors of tachometric parameters to the computer. The results of theoretical calculations were analyzed and the rational settings of the data transmission system were determined using the simulation model of data. Originality. The study to determine and theoretically calculate the main characteristics of the data transmission channels from the hardware converters of data signals of analog sensors of technological parameters to the computer showed that the system operates in the mode of actual «non-maintenance». For more detailed studies of the processes occurring in the transmission system of tachometric data, an imitation model was created in the Matlab environment. This model allowed carrying out a number of experiments. Practical value. On the basis of experiments with the model, rational ways of solving the existing problem of the system operation in the mode of actual «non-maintenance» were established. Also, the introduction of one of the proposed methods for solving the problem or combining them requires further research in the real system